Necklace-Type Transmitter Attachment Method for Ruffed Grouse Chicks - Christopher A. Dobony; Brian W. Smith; John W. Edwards; Thomas J. Allen (National Quail Symposium Proceedings, 2017)
Although methodologies to obtain cause-specific mortality and survival information for adult ruffed grouse (Bonasa umbellus) are well documented, procedures for determining similar parameters are lacking for grouse chicks. Mortality among grouse chicks is believed highest during the first few weeks posthatch. During 1999-2002, we equipped ruffed grouse chicks (n = 97) from 33 separate broods, ≤ 4-days-old with radio transmitters to assess the efficacy of transmitters and to examine survival/mortality. Further, we observed that grouse chicks retained transmitters (100%) until recapture or mortality. Handling time was limited because transmitter attachment took only a few minutes per brood. We observed mortality fates for 91% of radio-collared chicks. Therefore, because of the non-intrusive nature, field application, and retention of necklace-style transmitters employed in this study, this method may provide a desirable alternative to assessing survival/mortality among ruffed grouse chicks.
Keywords: Bonasa umbellus; necklace-type collar transmitter; ruffed grouse chicks; West Virginia